Potential of moringa fruit (moringa aloifera lamk) seeds as an anti-inflammatory agent of oral cavity lesion - Bahruddin Thalib; Nurhayaty Natsir; Alqarama M. Thalib; Delvi S. Reni; Asmawati; Fajriani (DiscoverSys Inc., 2021)
Objective: To know the potential of moringa fruit seed extract (moringa Aloifera Lamk) as an anti-inflammatory agent of oral cavity lesion.Methods: One of the natural ingredients that are widely obtained in South Sulawesi is moringa plants and from several researches this plant has been proven to have a variety of properties. Moringa fruit extracts contain components in the form of flavonoids, saponins and tannins. The content serves as an antibacterial and anti-inflammatory. Wound is the loss or partial damage of tissues on the body, one form of wounds that occur in the gingival is a lesion due to irritation, traumatic wounds or wounds due to preoperative incision in the extraction of impacted teeth.Results: Therefore, a natural ingredient that is easily obtained at a low price and not a b-ingredient that is made from chemicals that will provide negative effects such as hypersensitivity and resistance for those who use these drugs.Conclusion: Moringa Oleifera Lamk seed oil has an effect on the formation of collagenase and an increase in the amount of fibroblast so that it has the potential to become an anti-inflammatory drug of the oral cavity.